2019
DOI: 10.1097/cmr.0000000000000515
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune cell infiltration in melanoma metastases affects survival and is associated with BRAFV600E mutation status

Abstract: Little is known about the infiltrative pattern of innate immune cells in primary melanoma compared with their paired metastases and in BRAFV600E-mutated tumors. Therefore, our aim was to characterize the inflammatory microenvironment in primary ulcerated and nonulcerated melanomas and paired metastases, to investigate the relation between inflammation and BRAFV600E mutation in primary melanoma and paired metastases, and to evaluate the effect of the analyzed biomarkers on melanoma-specific survival. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…In addition, males with melanoma generally have worse outcomes than females [33], which can partially be explained by the sex-related differences in the interaction between immune function and tumor biology [34]. Our findings that immune infiltration was significantly associated with multiple pathological features, including tumor staging, tumor site, ulceration and tumor thickness, are largely in line with the findings of previous studies [27,[35][36][37]. We also revealed that immune infiltration, not stromal infiltration, was positively correlated with patient survival.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, males with melanoma generally have worse outcomes than females [33], which can partially be explained by the sex-related differences in the interaction between immune function and tumor biology [34]. Our findings that immune infiltration was significantly associated with multiple pathological features, including tumor staging, tumor site, ulceration and tumor thickness, are largely in line with the findings of previous studies [27,[35][36][37]. We also revealed that immune infiltration, not stromal infiltration, was positively correlated with patient survival.…”
Section: Discussionsupporting
confidence: 90%
“…It has been recently reported that the occurrence of BRAF mutation is associated to an increased pDC infiltration compared with BRAF-wild type melanomas [208]. Our findings further expand the notion showing that pDC density is significantly reduced in NRAS p.Q61-mutated PCM, likely depending on the limited ability of NRAS-mutated melanoma cells to chemoattract pDCs [209].…”
Section: Clinical Relevance Of Melanoma-associated Pdcssupporting
confidence: 86%
“…Contexture of the innate immune components is emerging as relevant in shaping the adaptive immune responses in PCM subtypes. Notably, BRAF V600E PCM and distant metastasis exhibited an increased pDC numbers compared with BRAF-negative [208]. Moreover, we found a significant reduction in pDC density in NRAS + and NF-1 + PCM, particularly when compared with the BRAF + subgroup, whereas no differences were observed in CD8 + T-cell infiltration between TCGA subgroups [206,209].…”
Section: Melanoma As a Model Of Hypermutated Hot Tumormentioning
confidence: 51%
“…There was no significant difference in tumor volume between the two groups during the early stages of the experiment; however, the difference became significant after the 21st day. At the end of the study, the mean volume of the treatment group and the control group were 503:46 ± 45:13 mm 3 and 698:40 ± 87:96 mm 3 , respectively (P < 0:05; Table 2). In addition, during this period, mice from both groups had a normal appetite and there was no significant difference in body weight between the two groups.…”
Section: Effect Of Huaier On Tumor Growth In Nude Micementioning
confidence: 94%
“…Despite advances in the treatment of melanoma, MM has a very poor prognosis with invasion and metastasis remaining the leading cause of death [2]. Treatments with fewer adverse effects, improving the quality of life, and maximizing survival are an important part of the treatment of malignant metastatic melanoma [3]. Traditional Chinese medicine (TCM) has been used in China for many years and has many advantages such as low price, overall conditioning, and fewer adverse effects.…”
Section: Introductionmentioning
confidence: 99%